Effect of fatigue on the structural response of complex joint for offshore structures - Chow, Wan Han (2008)
Fatigue in offshore structures is caused by the cumulative effect of variable environmental loads experienced by the structure during its life. Both the global loading on the structure and the local loading on individual members contribute to fatigue damage. Fatigue damage is a highly localized phenomenon affected by local details in the structure. Fatigue failure occurs under repeated cycles of relatively low stress levels due to the growth of the internal cracks. Fatigue analysis is normally perform on jacket (steel framed tubular structure connected to the sea bed by piles which are driven through piles on the outer members of the jacket) subjected to repetitive wave loading. However for this project, emphasis is placed on evaluation of fatigue damage on a semisubmersible topsides (steel framed structure above the mean sea level) subjected to inertia loads resulting from wave loads. This project will focus on the classical method of fatigue analysis as well as the simplified fatigue analysis method. This project is mainly concerned with the fatigue damage experienced by the topsides complex joint subjected to inertia loads under the calm condition, extreme storm condition and damage storm condition. The main objectives are to demonstrate the applicability of using a simplified fatigue analysis spreadsheet in estimating the fatigue life of the complex joint. Besides that, calculation of hot spot stress by Finite Element Analysis and fatigue calculation based on Stress Concentration Factor (SCF) and S-N Curve is being performed. The fatigue remedy action and recommendations will also be addressed and discussed.